The potential ethnomedicine plant of Impatiens balsamina leaves from Pontianak, West Kalimantan, Indonesia for wound healing - HARIYANTO IH; INARAH FAJRIATY; TANTO WIJAYA; MUHAMMAD HAFIZH (Smujo International, 2018)
Abstract. Hariyanto IH, Fajriaty I, Wijaya T, Hafizh M. 2018. The potential ethnomedicine plant of Impatiens balsamina leaves from Pontianak, West Kalimantan, Indonesia for wound healing. Nusantara Bioscience 10: 58-64. Pacar air or garden balsam (Impatiens balsamina L.) is a herb plant that grows wildly in high humidity areas. The leaves of I. balsamina are used by the people in Bengkulu, Indonesia, as herbal medicine to treat wounds. I. balsamina grows abundantly in West Borneo due to the proper conditions. This study aimed to determine the wound healing activity of I. balsamina as an ethnomedicine plant and standardize its extract. The leaves of I. balsamina was macerated with 96% ethanol. The extraction yield was 20.3%, the solubility of the extract in water and ethanol was 15.77% and 41.41%, respectively, the drying rate was 23.02%, and the extracted density was 0.8136 g/mL. The extract of I. balsamina contained polyphenols, flavonoids, saponins, tannins, quinones, steroids, and terpenoids based on the phytochemical screening. Anatomical and histological pathology tests showed that the leaves extract had the potential to heal the external wound.